Cholesterol-induced toxicity: An integrated view of the role of cholesterol in multiple diseases - Song, Yongfeng; Liu, Junjun; Zhao, Ke; Gao, Ling; Zhao, Jiajun (Cell metabolism, 2021)
High levels of cholesterol are generally considered to be associated with atherosclerosis. In the past two decades, however, a number of studies have shown that excess cholesterol accumulation in various tissues and organs plays a critical role in the pathogenesis of multiple diseases. Here, we summarize the effects of excess cholesterol on disease pathogenesis, including liver diseases, diabetes, chronic kidney disease, Alzheimer’s disease, osteoporosis, osteoarthritis, pituitary-thyroid axis dysfunction, immune disorders, and COVID-19, while proposing that excess cholesterol-induced toxicity is ubiquitous. We believe this concept will help broaden the appreciation of the toxic effect of excess cholesterol, and thus potentially expand the therapeutic use of cholesterol-lowering medications. Here, Song et al. present a concept called “cholesterol toxicity,” which stems from the emerging evidence of adverse effects of excess cholesterol in multiple organs. They suggest that excess cholesterol contributes to the pathogenesis of several diseases other than atherosclerosis. This concept potentially expands the therapeutic use of cholesterol-lowering medications.